2016
DOI: 10.1080/17453674.2016.1199146
|View full text |Cite
|
Sign up to set email alerts
|

Palacos compared to Palamed bone cement in total hip replacement: a randomized controlled trial

Abstract: Background and purposeStability and survival of cemented total hip prostheses is dependent on a multitude of factors, including the type of cement that is used. Bone cements vary in viscosity, from low to medium and high. There have been few clinical RSA studies comparing the performance of low- and high-viscosity bone cements. We compared the migration behavior of the Stanmore hip stem cemented using novel low-viscosity Palamed bone cement with that of the same stem cemented with conventional high-viscosity P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nowadays, people are having a much longer life expectancy, and it is expected that people >65 years will reach 21.1% of the population by the end of 2050 . The increasing aging population has also led to a greater demand for hard tissue implants (bone and dental, in particular), as elderlies are more prone to severe musculoskeletal diseases and dental problems. On the other hand, the demand for hard tissue implants by younger patients (<65 years) cannot be underestimated, taking into account the incidence of accidents, diseases, and the increasing demand in cosmetic surgeries.…”
mentioning
confidence: 99%
“…Nowadays, people are having a much longer life expectancy, and it is expected that people >65 years will reach 21.1% of the population by the end of 2050 . The increasing aging population has also led to a greater demand for hard tissue implants (bone and dental, in particular), as elderlies are more prone to severe musculoskeletal diseases and dental problems. On the other hand, the demand for hard tissue implants by younger patients (<65 years) cannot be underestimated, taking into account the incidence of accidents, diseases, and the increasing demand in cosmetic surgeries.…”
mentioning
confidence: 99%
“… 2005 , Molt and Toksvig-Larsen 2014 , Henricson and Nilsson 2016 , Meinardi et al. 2016 ). RSA research is costly and tedious work, and it is not always possible to recruit enough patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, the perception of poor results from low-viscosity cements led to favoring of higher-viscosity cements such that by 2006, 82% of surgeons in the United Kingdom were using high-viscosity cement 15,35 . Regardless, a sizeable minority of surgeons continued to favor low-viscosity and medium-viscosity cements, arguing for a superior penetration into the trabecular bone and stem-cement bonding enhancement 15,36,37 . More recently, a randomized controlled trial comparing low-viscosity and high-viscosity cements found no significant difference in stem migration using radiostereometric analysis 36 .…”
Section: Cement Properties and Preparationmentioning
confidence: 99%